Evaluation of the usefulness of cluster analysis in the identification of motor ability structure in leading Polish badminton players from different age categories - Zak, M.; Jaworski, J.; Lech, G. (Journal of Kinesiology and Exercise Sciences, 2015)
Study aim. The main aim of the study was to identify clusters of players with similar motor ability profiles from a group of badminton players at different calendar ages. In addition, the level of significant differences was determined in terms of the analysed variables between the particular groups. Study design. The study was conducted among a group of at 30 most highly classified badminton players (youngsters 11-13 years, younger juniors 14-16 and juniors 17-19 years). The scope of research included 19 variables from the group of condition and coordination abilities. Statistical analysis used the k-means method as well as one-way ANOVA variance analysis. Results and conclusions. On the basis of cluster analysis, the first cluster was assigned 6 juniors and 2 younger juniors (cluster 1 - juniors), the second: 7 younger juniors, 5 juniors and 1 youngster (cluster 2 - younger juniors), the third: 8 youngsters and 1 younger junior (cluster 3 - youngsters). The k-means method made it possible to identify separate clusters with similar motor capacity in the group of badminton players. On this basis, evaluation of the cluster content was conducted, as well as the affiliation of players from different calendar age categories. In the master model, a very important role is played by anaerobic and aerobic capacity as well as motor skill coordination with a higher degree of organization.